Seven crashes the economic crises that shaped globalization - James, Harold 1956- (Yale University Press, 2023)
Introduction: How Prices Shape Globalization -- 1 The Great Famine and the Great Revolt -- 2 Krach at the Margins -- 3 The Great War and the Great Inflation -- 4 The Great Depression -- 5 The Great Inflation: The 1970s -- 6 The Great Recession: 2008 -- 7 The Great Lockdown: 2020-2022 -- Conclusion: The Next Great Globalization